The Putative Endonuclease Activity of MutL Is Required for the Segmental Gene Conversion Events That Drive Antigenic Variation of the Lyme Disease Spirochete - Castellanos, Mildred; Verhey, Theodore B.; Goldstein, Madeleine; Chaconas, George (Frontiers in Microbiology, 2022)
The Lyme disease spirochete Borrelia burgdorferi, encodes an elaborate antigenic variation system that promotes the ongoing variation of a major surface lipoprotein, VlsE. Changes in VlsE are continual and always one step ahead of the host acquired immune system, which requires one to two weeks to generate specific antibodies. By the time this happens, new VlsE variants have arisen that escape immunosurveillance, providing an avenue for persistent infection. This antigenic variation system is driven by segmental gene conversion events that transfer information from a series of silent cassettes (vls2-16) to the expression locus, vlsE. The molecular details of this process remain elusive. Recombinational switching at vlsE is RecA-independent and the only required factor identified to date is the RuvAB branch migrase. In this work we have used next generation long-read sequencing to analyze the effect of several DNA replication/recombination/repair mutants on the frequency of gene conversions at vlsE. We report a requirement for the mismatch repair protein MutL and specifically the MutL endonuclease activity for switching at vlsE. This is the first report of an unexpected essential role for MutL in a bacterial recombination system and expands the known function of this protein as well as our knowledge of the details of the novel recombinational switching mechanism for vlsE variation.